SISTEM PIDANA MATI MENURUT HUKUM POSITIF DAN HUKUM ISLAM - Faisal Faisal (IAIN Langsa, 2017)
The capital punishment system is one of the legal system system in which it contains about capital punishment. Even in practice that occurs in various legal systems it is also very diverse. In Indonesia there are actually some differences in the legal system. For example in Indonesia today there are laws that apply formally and Islamic law. The purpose of punishment according to the draft Penal Code is stated in article 54, namely: 1) Prevent the commission of criminal acts by upholding the legal norms for the sake of community protection. 2) To popularize the convict by conducting coaching so as to make him a good and useful person. 3) Resolving conflicts caused by criminal acts, restoring balance and bringing a sense of peace in society. 4) Release the guilt of the convicted person. While the implementation of Islamic law, namely: the primary purpose (al dharury), secondary goals (al haajiy), tertiary goals (al tahsiniyyat). In Islam the death penalty is explicitly described in the Qur'an or hadith, it is found in four cases, namely those who commit adultery Mukhshan, killing intentionally, hirabah and apostasy (out of Islam). And Also known in Islam that the death penalty for ta'zir is if the death penalty is desired by the public, for example for espionage (spy) and a very dangerous recidivist.